2011
DOI: 10.1177/0194599810396790
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Injuries Due to Golf Cart Trauma

Abstract: Golf cart trauma can cause significant craniofacial injuries, particularly in the pediatric population and in adults who consume alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…Karting is one of the sports that causes head injuries. In a study of 68 cases of craniofacial trauma in the sport, Miller et al 1 reported 69% of lesions of the skull. They also discovered 32% of such cases had fractures of the skull and facial bones while 20.6% of cases had intracranial hemorrhages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karting is one of the sports that causes head injuries. In a study of 68 cases of craniofacial trauma in the sport, Miller et al 1 reported 69% of lesions of the skull. They also discovered 32% of such cases had fractures of the skull and facial bones while 20.6% of cases had intracranial hemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…This is more common among teens in the Western World. 1 In our own local settings, these types of sports are practiced by children from relatively affluent backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review [5], Augron et al categorized powered mobility devices, as well as MMS benefits into: 1) effectiveness (e.g., body function, participation and activity); 2) social significance (e.g., caregiving and cost); and 3) subjective well-being (e.g., quality of life and satisfaction). Within this review, 19 studies were determined to demonstrate the benefits of using powered mobility devices in all three categories.…”
Section: Introductionmentioning
confidence: 99%
“…These devices have recently grown in popularity because of their small size, low maintenance, and ease of use; however, new models have become faster, quieter and more powerful. These factors have led to several safety issues, especially for "older adults" (over 80-years old) [16,18,19]. According to the National Electronic Injury Surveillance System database, over 147,500 golf cart-related injuries occurred from 1990 to 2006 in the United States, with an increase of ~130% during these 17 years [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation